2017
DOI: 10.1109/jphotov.2016.2646421
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Open Volume Deficiencies in Hydrogenated Amorphous Silicon During Annealing

Abstract: • A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 83 publications
(85 reference statements)
3
24
0
Order By: Relevance
“…This difference in size distribution can be the reason for the observed difference in the broadening parameter B r in the Tauc-Lorentz analysis, i.e., the less disordered and more relaxed 50 C sample allows for a wider size distribution of open volume deficiencies in the material. Furthermore, the size distribution difference after annealing is in line with the idea that agglomeration and effusion of open volume deficiencies take place less efficiently in denser materials, 42 which-in this work-are the films deposited at higher temperatures. It can thus be argued that the final annealed state of the sample deposited at 10 C is characterized by a narrower distribution of large open volume deficiencies in comparison to the 50 C sample.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This difference in size distribution can be the reason for the observed difference in the broadening parameter B r in the Tauc-Lorentz analysis, i.e., the less disordered and more relaxed 50 C sample allows for a wider size distribution of open volume deficiencies in the material. Furthermore, the size distribution difference after annealing is in line with the idea that agglomeration and effusion of open volume deficiencies take place less efficiently in denser materials, 42 which-in this work-are the films deposited at higher temperatures. It can thus be argued that the final annealed state of the sample deposited at 10 C is characterized by a narrower distribution of large open volume deficiencies in comparison to the 50 C sample.…”
Section: Resultssupporting
confidence: 80%
“…Interestingly, this is in line with the findings in an annealing study of various a-Si:H bulk materials where it was found that the migration of open volume deficiencies evolves more efficiently in less dense materials. 42 Note that on long timescales, all the samples indeed show a decrease in lifetime, hinting at depassivation of the a-Si:H/c-Si interface caused by the breaking of Si-H bonds at the c-Si surface. The samples prepared at 75 and 100 C did not show any passivation both in the as-deposited state and after annealing due to the occurrence of epitaxy, and have therefore not been investigated further.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Consequently, the relation between these metastable properties and the optical properties (refractive index, n and extinction coefficient, k ) was characterized using spectroscopic ellipsometry (SE), predominantly in the UV spectrum . While considerable scientific effort has been spent on investigating the phenomenon in photovoltaic cells, its potential application for reconfigurable photonics by exploiting the metastable optical properties has remained unexplored …”
Section: Introductionmentioning
confidence: 99%